Implementation of informatics organizations process as a competence on the informatics professional formation - González Hernández, Walfredo (2016)
The implementation is one of the more important activities in the engineers' activity. In this article, the author assumes theoretic positions of the bibliography looked up on the implementation process and his classifications. In addition, the information-technology curriculum's essential elements in the world and the importance of implementation in them are assumed. In the last paragraph, the article examines how structuring the implementation as essential element in the mode of acting of the information-technology professional.